HUBUNGAN PENGETAHUAN IBU DAN MOTIVASI IBU TERHADAP KUNJUNGAN POSYANDU DI PUSKESMAS BENGKULU - Selvia Novita Sari; Charles Ananda (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
IHC was established in order to provide health services, especially in disease prevention, familyplanning services, and can help reduce maternal mortality and infant mortality. Muara Marashealtcenter is one of the health centers located in Seluma. Based on the initial survey in 7 mothers wereinterviewed at random on the role and functions of Posyandu, found 5 people who do not know theprogram of work and program information Posyandu activities in the health service and the type ofhealth care that can be provided by posyandu The purpose of this study was to determine therelationship of mother's mother's knowledge and motivation to visit Posyandu in Muara Marashealth centerDistrict of Semidang Alas Maras Seluma Bengkulu. The results show there are 66%of respondents with low knowledge and obtained p value = 0.004 <0.05 which means that there isa relationship between mother's knowledge and posyandu visits while 54% of respondents withlow motivation and 60% of respondents and low visit rate with p value = 0 , 01 <0.05 which showsthat there is a relationship between maternal motivation and posyandu visits